Electrochemical deposition of Pt nanoparticles on carbon nanotube patterns for glucose detection - Zeng, Zhiyuan (2012)
Single-walled carbon nanotube (SWCNT) microarrays are successfully patterned on SiO2 substrates based on an evaporation-induced self-assembly mechanism. On these SWCNT micropatterns, the highly electroactive polycrystalline Pt nanoparticles (PtNPs) are deposited by using the electrochemical method. The obtained PtNP-SWCNT nanocomposites exhibit a low detection limit for hydrogen peroxide (4 µM). The further investigation on a glucose oxidase (GOx)/BSA/PtNP-SWCNT based biosensor indicates that the detection limit and sensitivity for glucose are 0.04 mM and 4.54 µA mM^-1 cm^-2, respectively. Our results prove that the improved electrocatalytic activity originates from the PtNP-SWCNT micropatterns, which provide a potential platform to immobilize different enzymes used for bioelectrochemical applications.